UPAYA MENINGKATKAN KEPERCAYAAN DIRI SISWA MELALUI METODE PROBLEM-BASED LEARNING PADA SISWA KELAS VII D - Yunita Sari; Noviyanti Kartika; Wiwik Setyowati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Self-confidence is an essential aspect of students' development that supports academic achievement, communication, and social interaction. The results of the Student Needs Assessment Questionnaire (Angket Kebutuhan Peserta Didik [AKPD]) administered to Grade VII D students at SMPN 11 Madiun indicated that most students had low levels of self-confidence, highlighting the need for guidance services to foster their confidence in their own abilities. This study aimed to improve students' self-confidence through the implementation of the Problem-Based Learning (PBL) model in classical guidance services. The study employed a Guidance and Counseling Action Research (PTBK) design conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The participants were 31 Grade VII D students. Data were collected using a self-confidence questionnaire and analyzed descriptively. The results showed a gradual improvement in students' self-confidence, increasing from 49% in the pre-action stage to 65% in Cycle I and 78% in Cycle II. In addition, students became more actively involved in group discussions, more willing to express their opinions, more confident in interacting with their peers, and more confident when presenting the results of group discussions. Therefore, the implementation of the Problem-Based Learning model was effective in improving students' self-confidence.